2010
DOI: 10.3112/erdkunde.2010.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic pattern of species diversity on the Canary Islands

Abstract: Summary:We use an island specific presence/absence data set for the Canary Islands' Arthropoda, Spermatophyta, Fungi, Lichenes, Bryophyta, Mollusca, Chordata, Pteridophyta, Annelida and Nematoda to assess the relative influence of environmental and historical factors on species distribution and endemism. Species richness and the percentage of island endemic species as well as similarity indices for island comparisons were calculated for all species groups. Hierarchical partitioning is used to identify the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Crete is longer isolated than many oceanic islands, e.g. the current high islands of the Hawaiian archipelago range in age from 5.1 to 0.5 My [63], while the Canary Islands from 20 to 1.1 My [64]. For a detailed account of the palaeogeography of Crete see [65]–[67].…”
Section: Methodsmentioning
confidence: 99%
“…Crete is longer isolated than many oceanic islands, e.g. the current high islands of the Hawaiian archipelago range in age from 5.1 to 0.5 My [63], while the Canary Islands from 20 to 1.1 My [64]. For a detailed account of the palaeogeography of Crete see [65]–[67].…”
Section: Methodsmentioning
confidence: 99%
“…Distance-decay relations are frequently calculated using log-transformed similarity values, log transformed distance values or both. Most studies dealing with plants use an untransformed relationship [22,47]. Untransformed relations have the advantage of clear interpretation and comparison but bear the problem that: (a) the fitted line has an intercept with the x-axis implying negative similarity values after a certain distance; and (b) that the fitted line has an intercept with the y-axis implying negative distances for specific similarity values.…”
Section: Discussionmentioning
confidence: 99%
“…The habitat diversity hypothesis (also the habitat heterogeneity hypothesis, Williams 1964) has been proposed to complement the area per se hypothesis (included in the equilibrium theory of island biogeography, MacArthur and Wilson 1967). It has also been suggested that island elevation might describe the carrying capacity of volcanic islands (Price 2004, Steinbauer andBeierkuhnlein 2010) and hence be a suitable proxy for habitat diversity (Kreft and Jetz 2007). Indeed, adding habitat diversity to the species richness-area model has been shown to improve the descriptive power of models for several archipelagos (e.g.…”
Section: Island Area Vs Habitat Diversitymentioning
confidence: 99%
“…Also Steinbauer and Beierkuhnlein (2010) have found that compositional similarity between the Canary Islands in many species groups is best explained by their geographic distance and Sanmartín et al (2008) have shown Canary plant and invertebrate phylogenetic patterns to be best explained by interisland dispersal between neighbouring islands. By relocating the islands in the archipelago while maintaining the overall connectivity of the archipelago more or less stable with the help of convex hull restriction, we found real archipelago configuration to be important in creating realistic species composition patterns but not species richness.…”
Section: Effect Of Archipelago Spatial Configurationmentioning
confidence: 99%